Development of an SMS-based library querying system for the UP Integrated School Library - Cadiz, Paolo Leandro S. (2013)
With the current pace in development of mobile technologies, more people are starting to demand for mobile services. Librarians are no exemption from this demand, as seen in mobile journals and online articles, the demand for mobile library services is increasing, with people requesting that book searching and borrowing, as well as reference querying be made mobile for easy access wherever they go. The viable solution to the library users' demand is the use of Short Messaging Services, or text messaging as a medium to deliver these mobile library services.